Att vara eller inte vara? Nationalstatens Roll i en Globaliserad Värld - Långberg,Johan (2005)
Globalization is one of the most popular catchphrases in the international relations debate today. Globalization is a complex concept with as many definitions as authors. National borders or jurisdictions do not control the phenomenon, instead, it is moving without restraints from region to region. Is this a threat to the sovereignty of nation-state and an end of the system of Westphalia? Does the globalization undermine the nation-state by increased factor-mobility, less tax revenue and participations multilateral co-operations, as the globalists think? Or is it strengthens its importance by offering better allocation of resources through free and healthy competition, as the skeptics believe. The aim of this thesis is to analyze theories of globalization by applying them on Sweden and the Netherlands. The use of institutionalism has provided useful tools in the investigation of my topic. My conclusion is that it is not globalization it self that has lead to institutional changes within either Sweden or the Netherlands. The participation in multilateral co-operations, which are to be seen as part of globalization since they erasing national borders, has lead to the most significant changes in national institutions. Therefore, it is these regional projects that are limiting the autonomy of the states.
Keywords: globalisering; nationalstat; Sverige; Holland; institutionalism; Political and administrative sciences; Statsvetenskap, förvaltningskunskap